2021
DOI: 10.1002/adem.202100689
|View full text |Cite
|
Sign up to set email alerts
|

3D Computed Tomography Quantifies the Dependence of Bulk Porosity, Surface Roughness, and Re‐Entrant Features on Build Angle in Additively Manufactured IN625 Lattice Struts

Abstract: Layer‐by‐layer additive manufacturing (AM) by means of laser‐powder bed fusion (L‐PBF) offers many prospects regarding the design of lattice structures used, for example, in gas turbines. However, defects such as bulk porosity, surface roughness, and re‐entrant features are exacerbated in nonvertical structures, such as tilted struts. The characterization and quantification of these kinds of defects are essential for the correct estimation of fracture and fatigue properties. Herein, cylindrical struts fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…The differences in the obtained RS are small and well within the error bar of the measurements. This corroborates the assumption made by Mishurova et al (2018), Serrano-Munoz, Fritsch et al (2021) and Thiede et al (2018). Most probably, the mild texture of the 311 reflection (maximum 1.6 m.r.d.)…”
Section: Figure 11supporting
confidence: 90%
See 3 more Smart Citations
“…The differences in the obtained RS are small and well within the error bar of the measurements. This corroborates the assumption made by Mishurova et al (2018), Serrano-Munoz, Fritsch et al (2021) and Thiede et al (2018). Most probably, the mild texture of the 311 reflection (maximum 1.6 m.r.d.)…”
Section: Figure 11supporting
confidence: 90%
“…Similar observations have been made for PBF-LB/M/IN625 structures, where the principal direction coincides with the main geometrical axis of the structure (Fritsch et al, 2021). However, Fritsch et al (2021) showed that the determination of the principal stress is only independent of the choice of the measurement directions if one uses nine directions.…”
Section: The Scanning Strategy Determines the Rs Distributionsupporting
confidence: 73%
See 2 more Smart Citations
“…A detailed study of the roughness is, however, beyond the scope of the present work, as it would require many more data. [ 30 ] The results in Figure 7 and 8 show that the major portion of the damage is initially caused by the hydrogen charging procedure and little additional damage is introduced during plastic deformation (specimen B). However, a significant amount of damage (observed by SXRCT) arises at large elongations, i.e., shortly before failure (specimen C).…”
Section: Resultsmentioning
confidence: 99%